Open Volar STT Ligament Reconstruction to Augment the Mathoulin's Arthroscopic Dorsal Capsuloligamentous Reconstruction: Technique Description and Case Reports - Smith, Nicholas Charles; Yates, Sally E.; Mettyas, Tamer (Journal of Wrist Surgery, 2023)
Background The results of Mathoulin's arthroscopic dorsal capsuloligamentous reconstruction (ADCLR) are excellent in many patients with scapholunate instability, though less consistently good in higher grade instabilities. The purpose of this article is to describe a novel technique of volar scaphotrapeziotrapezoid (STT) reconstruction which may be used to augment rotational control of the scaphoid, in conjunction with the ADCLR, for use in European Wrist Arthroscopy Society (EWAS) grade IV/V instabilities.Description of Technique Following completion of ADCLR, the STT joint is approached through the flexor carpi radialis sheath. The palmaris longus tendon is harvested. Fluoroscopy is used to site guide wires for tunnel placement in the distal scaphoid and the proximal trapezium; 3.5-mm tunnels are overdrilled in both bones, to a depth of 8 mm. The palmaris graft is then anchored in the scaphoid tunnel with a mini-DX SwiveLock anchor. The graft is tensioned, then anchored in the trapezium tunnel with another anchor.Patients and Methods We retrospectively selected two young men heavy manual workers who had this procedure more than 12 months previously for scapholunate instability, with static radiographic abnormalities and a drive through sign (EWAS grade V). The patients were reviewed after 12 months, for assessment of visual analog scale, quick disabilities of the arm, shoulder, and hand, and patient-rated wrist/hand evaluation scores, range of motion, and grip strength.Results Both patients had marked improvements of wrist comfort and function at 1 year, and were able to return to their normal duties at work and complete all activities of daily living with minimal symptoms.Conclusion This volar STT reconstruction may expand the success of the Mathoulin's ADCLR into higher grade instabilities.
Keywords: scapholunate instability; Mathoulin's ADCLR; volar STT reconstruction; scapholunate instability